Green Synthesis of Silver Nanoparticles Using Extract of Kluwih Leaves (Artocarpus camansi Blanco.) by Microwave-Assisted Irradiation and Their Antibacterial Properties - Siregar, Nina Ashariani; Putra, Effendy De Lux; Sinaga, Siti Morin; Satria, Denny; Waruwu, Syukur Berkat (Indonesian Journal of Applied Research (IJAR), 2024)
Nanoparticles are particles measuring 1-100 nm that were synthesized using metals, and silver was a commonly used metal because of its potential as an antibacterial agent. Physical and chemical methods were often used in synthesis but are less environmentally friendly. Alternatively, biological processes that utilize phytochemical compounds as reducing agents are preferred. One of the plants rich in phytochemical compounds was kluwih leaves (Artocarpus camansi Blanco). This study aimed to synthesize silver nanoparticles (AgNPs) mediated by kluwih leaves using microwave irradiation. Characterization of nanoparticles was carried out by visual observation and using UV-Vis spectrophotometry. Antibacterial activity was evaluated by determining MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration), followed by examining DNA and protein leakage and biofilm formation using a microdilution method against S. epidermidis and P. aeruginosa. The results showed that AgNPs from kluwih leaves had been successfully formed and could be used as reducing agents in AgNPs biosynthesis. Visual color changed, and analysis of UV-Vis spectrophotometry showed peaks at 441 nm. The results of the antibacterial evaluation showed MIC 1.90 µg/ml (S. epidermidis) and 7.80 µg/ml (P. aeruginosa) also caused cell leakage and reduced biofilm formation significantly at a concentration of 1/2 MIC. These results were promising for further development in future research.